Feasibility and Acceptability of an Early Childhood Obesity Prevention Intervention: Results from the Healthy Homes, Healthy Families Pilot Study - Akilah Dulin Keita; Patricia M. Risica; Kelli L. Drenner; Ingrid Adams; Gemma Gorham; Kim M. Gans (Hindawi Limited, 2014)
Background. This study examined the feasibility and acceptability of a home-based early childhood obesity prevention intervention designed to empower low-income racially/ethnically diverse parents to modify their children's health behaviors. Methods. We used a prospective design with pre-/posttest evaluation of 50 parent-child pairs (children aged 2 to 5 years) to examine potential changes in dietary, physical activity, and sedentary behaviors among children at baseline and four-month follow-up. Results. 39 (78%) parent-child pairs completed evaluation data at 4-month follow-up. Vegetable intake among children significantly increased at follow-up (0.54 cups at 4 months compared to 0.28 cups at baseline, P=0.001) and ounces of fruit juice decreased at follow-up (11.9 ounces at 4 months compared to 16.0 ounces at baseline, P=0.036). Sedentary behaviors also improved. Children significantly decreased time spent watching TV on weekdays (P<0.01) and also reduced weekend TV time. In addition, the number of homes with TV sets in the child's bedroom also decreased (P<0.0013). Conclusions. The findings indicate that a home-based early childhood obesity prevention intervention is feasible, acceptable and demonstrates short-term effects on dietary and sedentary behaviors of low-income racially/ethnically diverse children.